Hubungan Grit dan Ketangguhan Mental Pada Atlet Pencak Silat di Perguruan Tadjimalela Kota Bandung: Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara grit dan ketangguhan mental pada atlet pencak silat di Perguruan Tadjimalela Kota Bandung. - Wijayanti, Tanti; Rahmi, Upik; Suparto, Tirta Adikusuma (Universitas Hamzanwadi, 2025)
The purpose of this study was to analyze the relationship between grit and mental toughness in pencak silat athletes. This study used a descriptive correlational design with a cross-sectional approach. The population consisted of 60 pencak silat athletes who were selected using purposive sampling technique. Data were collected through the grit questionnaire and sport mental toughness questionnaire (SMTQ). The results showed that the level of grit of athletes was in the moderate category as many as 17 athletes (28.3%) and high as many as 43 athletes (71.7%). The distribution of the level of grit, it is known that out of a total of 60 martial arts athletes who were the subject of the study, none of the athletes were in the low grit category (0%). A total of 17 athletes (28.3%) were in the medium grit category, while the majority of athletes, namely 43 people (71.7%), showed a high level of grit. The bivariate test results using the Chi-Square correlation test showed a relationship between grit and mental toughness (p=0.000). The conclusion of this study states that there is a significant relationship between grit and mental toughness in pencak silat athletes.